DISPOSAL PRACTICES OF UNUSED AND EXPIRED PHARMACEUTICALS IN KARACHI AND THEIRIMPACT ON HEALTH AND ENVIRONMENT - Ahsaan Ahmed; Nousheen Mushtaq (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective: A large number of drugs going into the land fill or in water system have received great attention. In the present study, a survey was conducted to find out the household drug disposal practice and to determine the level of awareness regarding the proper method to discard these drugs. More than 80% volunteers reported the disposal practice through dustbin, 11.5% responds it is acceptable to flush them in sink or toilet, only 2% return them to pharmacy and 3.8% of the population do not have any background what to do with the expired or unused medication. To minimize the entry of pharmaceutical in environment proper guidance should be provided to the physician for prescribing less number of drugs in small amount moreover, public may be educated to discard the medicine safely.